2022
DOI: 10.1039/d1ma00988e
|View full text |Cite
|
Sign up to set email alerts
|

Helical SiNW design with a dual-peak response for broadband scattering in translucent solar cells

Abstract: Nanowires are widely used in the optics, optoelectronics, photocatalysis and photovoltaic because of its special optical properties. However, the narrow response spectrum of silicon nanowires (SiNWs) reduces the advantages of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…At present, it is found that further optimization of the symmetry of silicon nanowires can achieve good extinction of natural light. Gao [16] and other researchers designed a silicon nanowire with a three-leaf top view, which increased the extinction capacity of a single nanowire by 85%. The principle of the design is shown in Figure 7.…”
Section: Solar Energy Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it is found that further optimization of the symmetry of silicon nanowires can achieve good extinction of natural light. Gao [16] and other researchers designed a silicon nanowire with a three-leaf top view, which increased the extinction capacity of a single nanowire by 85%. The principle of the design is shown in Figure 7.…”
Section: Solar Energy Cellmentioning
confidence: 99%
“…The principle of the design is shown in Figure 7. Compared with cylindrical silicon nanowire arrays, the optical absorption of silicon nanowire arrays with three-leaf top view is improved by 23%, and the conversion efficiency of silicon nanowire solar cells is improved by 14.7% [16].…”
Section: Solar Energy Cellmentioning
confidence: 99%